1985
DOI: 10.1159/000249468
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin Allergy and the Relevance of Epicutaneous Tests

Abstract: Epicutaneous tests with penicillins are important in the evaluation of penicillin allergy in patients who have shown a delayed urticarial or maculo-papular rash after the administration of penicillin derivatives. Of 23 patients who showed positive epicutaneous tests only 5 also showed immediate-type reactivity upon subsequent intractuaneous tests with the major determinant of penicillin. Moreover, patients with positive epicutaneous tests were evidently immunologically reactive on penicillins, since lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…The most frequent reports of positive drug patch tests are related to the following drugs: betalactam antibiotics, especially amoxicillin (1,2,4,6,18,(24)(25)(26)(27)(28)(29)(30), cotrimoxazole (15), corticosteroids (1,31,32), heparin derivatives (1,(33)(34)(35)(36), pristinamycin (1,36), carbamazepine (1,2,20,(37)(38)(39)(40)(41)(42)(43)(44), diltiazem (1,45,46), diazepam (47), hydroxyzine (1,48), pseudoephedrine (1,21,22) and tetrazepam (1,16,(49)(50)(51).…”
Section: Commentmentioning
confidence: 99%
“…The most frequent reports of positive drug patch tests are related to the following drugs: betalactam antibiotics, especially amoxicillin (1,2,4,6,18,(24)(25)(26)(27)(28)(29)(30), cotrimoxazole (15), corticosteroids (1,31,32), heparin derivatives (1,(33)(34)(35)(36), pristinamycin (1,36), carbamazepine (1,2,20,(37)(38)(39)(40)(41)(42)(43)(44), diltiazem (1,45,46), diazepam (47), hydroxyzine (1,48), pseudoephedrine (1,21,22) and tetrazepam (1,16,(49)(50)(51).…”
Section: Commentmentioning
confidence: 99%
“…The most frequent reports of positive drug patch tests are related to the following drugs: betalactam antibiotics (Romano et al, 2002), especially amoxicillin (Barbaud et al, 1998b(Barbaud et al, , 2000Van Ketel, 1987, 1989;Bruynzeel et al, 1985;Romano et al, 1993Romano et al, , 1995Barbaud et al, 1997;Vega et al, 1991;Felix and Comaish, 1974), cotrimoxazole (Klein et al, 1995), corticosteroids (Barbaud et al, 1998b;Dooms-Goossens, 1995;Bircher et al, 1996;Kilpio and Hannuksela, 2003), heparin derivatives (Barbaud et al, 1998b;Bircher et al, 1990;Moreau et al, 1996;Figarella et al, 2001), pristinamycin (Barbaud et al, 1998bMichel et al, 1996), carbamazepine (Barbaud et al, 1998b(Barbaud et al, , 2000Vaillant et al, 1989;Silva et al, 1982;Camarasa, 1985;Romaguera et al, 1989;Jones et al, 1994;Rodriguez-Mosquera et al, 1991;Alanko, 1993;Corazza et al, 1995;Puig et al, 1996), diltiazem (Barbaud et al, 1998a(Barbaud et al, , 1993Romano et al, 1992;Cholez et al, 2003), hydroxyzine (Barbaud et al, 1998b;Michel et al, 1997), pseudoephedrine …”
Section: The Clinical Significance Of Drug Patch Testsmentioning
confidence: 99%
“…Patch testing with the suspected compound has been reported to be helpful in determining the cause of a CADR (Barbaud et al, 2001a(Barbaud et al, , 1998b(Barbaud et al, , 2000Osawa et al, 1990;Van Ketel, 1987, 1989;Barbaud, 2002Barbaud, , 2003Bruynzeel et al, 1985;Romano et al, 1993) and in studying the pathophysiological mechanisms involved in these reactions. The results of drug patch tests depend on the drug tested and the clinical features of the initial CADR (Barbaud et al, 1998b;Osawa et al, 1990;Bruynzeel and Van Ketel, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However, as we and others have shown, patch tests can be helpful for the aetiological diagnosis. [5][6][7][8][9][10][11][12][13][14][15] Osawa et al 14 have reported positive drug patch test results in 31·5% of cutaneous ADRs of nonimmediate type. More specifically, the positivity rates reported in the literature vary between 17% and 35% in investigated cutaneous ADRs caused by penicillin derivatives.…”
mentioning
confidence: 99%
“…More specifically, the positivity rates reported in the literature vary between 17% and 35% in investigated cutaneous ADRs caused by penicillin derivatives. 8,11 In spite of the interest of such investigations, the literature lacks prospective studies determining the value and specificity of drug skin tests in cases of cutaneous ADRs. Guidelines are also lacking concerning the procedure to use for each drug and the various clinical forms of cutaneous ADRs.…”
mentioning
confidence: 99%